Peran Pendidikan Islam Dalam Mewujudkan Generasi Unggul Dan Berkarakter - Fauzia, Adel Diba; Nizar, Alif Naf'an; Putri, Zahra Nindianti; Parhan, Muhamad (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Islamic education in general is an effort to help the growth and development of students so that they grow through the actualization of self-potential based on the rules of the Al-Qur'an and Hadith. This research uses a qualitative approach with a literature or library research type of research, the main objects are books or other literature sources which contain theories related to the discussion. The aim of this research is to determine the role of Islamic education in creating a generation of excellence and character. In forming a superior generation, Islamic education is very important because in Islam spiritual and moral values ​​are emphasized which support the ongoing process of forming good character, in accordance with religious teachings and in accordance with existing needs in society and globally. Formation of character and morals, strengthening spiritual values, integration of religious values ​​in speaking skills, as well as instilling the principles of justice are supporting aspects in creating a superior and characterful generation. Efforts to create a superior and characterful generation include strengthening learning of the Qur'an and Sunnah, instilling moral values, strengthening Islamic identity and identity, applying relevant and innovative learning methods, as well as creating a conducive educational environment.